How shoud competitive swimmers perform power swim-training? - Matsunami, M.; Taba, S.; Ichikawa, H.; Taguchi, M.; Taimura, A.; Funai, Y. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Power training in the pool (power swim-training) that provides a specific overload has been carried out as underwater resistance training. When performing the power swim-training, swimmers are instructed to continuously maintain a high stroke rate. However, if the stroke technique degrades, the training is be insufficient. The purpose of this study was to determine whether training performed in a high stroke rate is appropriate as power-swim training method. Method: Nine experienced collegiate sprint swimmers (5 male, 4 female, age 20.8±1.2 yrs.) were participated in this study. Each subject swam 25 m twice with maximum effort under three conditions: no load (SS), with load (PS), and with load and controlled stroke rate in SS (CPS), respectively. Power swimming with load was performed using the resistance tools (Swim Parachute, FINIS Inc., USA) that the swimmers use in their usual training. Moreover, the stroke rate was managed using a portable waterproofed metronome (Tempo Trainer, FINIS Inc., USA). The swimming time was measured in sections of 0 to 15 m, and 15 to 25 m, and the swimming velocity in each section was computed. The stroke rate was determined by measuring the duration of three strokes in the section of 15 to 25 m with a stopwatch. The stroke length was computed from the swimming velocity and stroke rate in the section of 15 to 25 m. Results: The stroke rate in PS (51.99±1.39 stroke/min) decreased significantly as compared with SS (55.16±1.07 stroke/min) (P<0.05). Although the stroke rate increased in CPS (55.07±1.07 stroke/min) significantly as compared with PS, there was no significant difference in swimming velocity between CPS (1.20±0.04m/s) and PS (1.18±0.03 m/s) in the 15-25 m section. In the 15-25 m section, the stroke length in PS was significantly longer (1.37±0.05 m/stroke) as compared with CPS (1.31±0.05 m/stroke) (P<0.05). Discussion: The results of this study showed that, in power swim-training, the training method of continuing to maintain a high stroke rate reduce stroke length. Therefore, the quality of the stroke technique degrades and it is supposed that there may be no suitable load for the active skeletal muscles. In conclusion, it is suggested that power swim-training to be performed by the swimmer`s own maximal effort is desirable method than controlled training to force a high stroke rate.